2019
DOI: 10.1111/hae.13917
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low‐dose factor VIII prophylaxis therapy on bone mineral density and 25(OH) vitamin D level in children with severe haemophilia A

Abstract: Background Decreased bone mineral density (BMD) is a significant morbidity in haemophilia. Vitamin D is important for the bone health of people with haemophilia. Regular factor VIII prophylaxis can prevent bleeding and arthropathy. Aim To determine the 25(OH) vitamin D level in severe haemophilia A patients and correlate it to their Hemophilia Joint Health Score (HJHS) and dual‐energy X‐ray absorptiometry (DEXA). We also compared the 25(OH) vitamin D and DEXA in haemophilia A and healthy children and in haemop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
(62 reference statements)
2
17
0
Order By: Relevance
“…The pathogenesis is multifactorial and includes reduced physical activity due to fear of trauma and bleeding, the presence of haemophilic arthropathy 10,14 and lack of weight‐bearing exercise during childhood and adolescence which is associated with a deficient peak bone mass 15 . Other factors such as hepatitis C virus (HCV) or human immunodeficiency virus (HIV) infections and their treatment may be independently associated with decreased bone mineral density (BMD), as well the extremely widespread vitamin D deficiency across all age groups and geographic areas 9,16‐18 …”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis is multifactorial and includes reduced physical activity due to fear of trauma and bleeding, the presence of haemophilic arthropathy 10,14 and lack of weight‐bearing exercise during childhood and adolescence which is associated with a deficient peak bone mass 15 . Other factors such as hepatitis C virus (HCV) or human immunodeficiency virus (HIV) infections and their treatment may be independently associated with decreased bone mineral density (BMD), as well the extremely widespread vitamin D deficiency across all age groups and geographic areas 9,16‐18 …”
Section: Introductionmentioning
confidence: 99%
“…To overcome this, Hua et al and Li et al studied the effects of low-dose prophylaxis and suggested that even low-dose prophylaxis can reduce ABR and improve the quality of life compared with episodic treatment [ 42 , 44 ]. A study by Andrawes et al reported that low-dose prophylaxis in severe hemophilia preserves bone mineral density (BMD), increases vitamin D levels, and decreases hemophilia joint health score (HJHS) [ 59 ]. Kavakli et al conducted a study on low- and high-dose prophylaxis; the results of the first 6 months indicated lower ABRs with high doses, but ABRs with both doses were comparable in the next 6 months [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…89 Low vitamin D levels have also been associated with decreased BMD, physical activity, quality of life and poor joint health. [90][91][92] These studies suggest that routine assessment of serum levels of vitamin D could guide early diagnosis of joint damage and treatment in patients with hemophilia, particularly in children. In patients with hemophilia, prevention of poor bone health should include primary prophylaxis, a diet rich in calcium and vitamin D, physiotherapy, and weight-bearing physical activities.…”
Section: Dovepressmentioning
confidence: 99%
“…In patients with hemophilia, prevention of poor bone health should include primary prophylaxis, a diet rich in calcium and vitamin D, physiotherapy, and weight-bearing physical activities. 52,[89][90][91]…”
Section: Dovepressmentioning
confidence: 99%